(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Growth of the gold loan NBFCs primarily occurred in the sense of an appreciation for gold, which confirmed the metrics of a sound financial condition, for example capital adequacy ratio, the Non-Performing Asset (NPA). NFBCs have become saturated with laws and legislation for gold loans and the resulting collapse in gold prices. In short, the sudden gold price correction will have a disastrous impact not just on NBFC Gold loans, but on the stock system as a whole.